Violating and Flouting the Conversational Maxims in Situation Comedy 2 Broke Girls: The Two Opening, Season 6, Episode 1 - Icih Safitri; Frina Diniarta Nur (ESENSI LINGUA, 2022)
This research aims at analyzing violation and flouting the conversational maxims that occurred in the situation comedy 2 Broke Girls: The Two Opening, Season 6, Episode 1. The study uses qualitative methods and intends to answer four research questions, i.e., kinds of maxims that are violated, kinds of maxims that are flouted, characters who violate and flout the maxims, and reasons of violating and flouting the maxims. The theory used is Grice’s theory of cooperative principle, conversational maxims, and implicature. This research used qualitative method. The result of the analysis showed that violation and flouting of the conversational maxims appeared in the 2 Broke Girls. Thirty-one data were found. Twelve data contains violation, and nineteen data contains flouting. All the maxims were violated and flouted, i.e., maxim quantity, quality, relation, and manner. The speaker violated and flouted the maxim for various reasons according to what maxim that was violated and flouted. Almost all characters violated and/or flouted the maxims.